1984
DOI: 10.2134/agronj1984.00021962007600050027x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Spring Wheat Leaf Growth Rates and Anthesis from Air Temperature1

Abstract: Seasonal variability in climate within and between the major spring wheat (Triticum aestivum L.) growing regions of the world causes large differences in plant development patterns. A major need of models attempting to describe crop growth as a dynamic process is an evaluation of phenological development. Researchers modeling growth and yield would benefit from a meteorologically-based phenological index that accurately and reliably predicts the development stage. The objective of this study was to develop cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
117
0
14

Year Published

1994
1994
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(148 citation statements)
references
References 15 publications
(21 reference statements)
17
117
0
14
Order By: Relevance
“…and when variations positive of temperature are sensed by the apical meristem, there is increase in the leaf elongation rate (Peacock, 1975). Duru & Ducrocq (2000) observed significant increases in leaf appearance rate and in the number of leaves with changes in the temperature, which indicates that this environmental factor is one of the most important in leaf appearance rate control (Bauer et al, 1984).…”
Section: Discussionmentioning
confidence: 94%
“…and when variations positive of temperature are sensed by the apical meristem, there is increase in the leaf elongation rate (Peacock, 1975). Duru & Ducrocq (2000) observed significant increases in leaf appearance rate and in the number of leaves with changes in the temperature, which indicates that this environmental factor is one of the most important in leaf appearance rate control (Bauer et al, 1984).…”
Section: Discussionmentioning
confidence: 94%
“…Os graus dias acumulados (GDA) foram utilizados como escala de tempo durante o enchimento do grão, porque a taxa de desenvolvimento da planta de trigo é determinada, predominantemente, pela temperatura (Bauer et al, 1984). No cálculo dos graus dias utilizou-se 5°C como temperatura base.…”
Section: Methodsunclassified
“…However, the differences were not significantly different. Water stress appears to have an impact on phyllochron, but only at extreme stress [21] [22]. [9] found that rice plants experience …”
Section: Phyllochron (D•leaf −1 )mentioning
confidence: 99%